EVALUASI KINERJA BANK SYARIAH INDONESIA SEBELUM DAN SETELAH KONSOLIDASI BERDASARKAN RASIO KEUANGAN DAN PERATURAN OTORITAS JASA KEUANGAN TAHUN 2019 – 2022 - Elmanizar, Elmanizar; Adji, Ario Setyo (Institut Rahmaniyah Sekayu, 2023)
This study aims to evaluate the financial performance of Bank Syariah Indonesia before and after consolidation based on financial ratios and the 2019-2022 Financial Services Authority Regulation. The indicators in this study use various financial ratios of Bank Syariah Indonesia, namely liquidity ratios, profitability ratios and capital adequacy ratios. The method used uses Comparative Analysis by comparing financial ratios before and after consolidation to understand financial conditions after consolidation, measure operational efficiency and assess financial performance. Based on the research results based on SEOJK Number 28/SEOJK.03/2019 standards, it shows that the NPF, FDR, and ROA ratios of Bank Syariah Indonesia after consolidation have better results than before consolidation and have a rating criterion of 1. Furthermore, the ROE and NOM ratios after consolidation have better results than Bank Syariah Indonesia before consolidation even though they have criteria for ranking 3 and ranking 5. The BOPO and CAR ratios after consolidation have very varied results but also indicate very good compared to Bank Syariah Indonesia before consolidation even though they have a rating criterion of 1.